Integrin-substrate interactions underlying shear-induced inhibition of the inflammatory response of endothelial cells - Luu, Thin N.; Glen, Katie E.; Egginton, Stuart; Rainger, Ed G.; Nash, Gerard B. (Thrombosis and Haemostasis, 2013)
Conditioning of endothelial cells by shear stress suppresses their response to inflammatory cytokines. We questioned whether signalling through different integrin-matrix interactions, previously associated with the pathogenic effects of disturbed flow, supported the anti-inflammatory action of steady shear. Primary human endothelial cells were cultured on different substrates and exposed to shear stress (2.0Pa) for varying periods before stimulation with tumour necrosis factor-α (TNF). Shear-conditioning inhibited cytokine-induced recruitment of flowing neutrophils. However, the effect was similar for culture on collagen, laminin or fibronectin, even when seeding was reduced to 2hours, and shear to 3hours before TNF treatment (to minimise deposition of endothelial matrix). Nevertheless, in short- or longer- term cultures, reduction in expression of β1-integrin (but not β3-integrin) using siRNA essentially ablated the effect of shear-conditioning on neutrophil recruitment. Studies of focal adhesion kinase (FAK) phosphorylation, siRNA against FAK and a FAK-inhibitor (PF573228) indicated that FAK activity was an essential component downstream of β1-integrin. In addition, MAP-kinase p38 was phosphorylated downstream of FAK and also required for functional modification. Mechanotransduction through β1-integrins, FAK and p38 is required for anti-inflammatory effects of steady shear stress. Separation of the pathways which underlie pathological versus protective responses of different patterns of flow is required to enable therapeutic modification or mimicry, respectively.
Keywords: Endothelial cells; shear stress; integrin; inflammation